Electricity generation by sliding an ionic solution droplet on a self-assembled reduced graphene oxide film. Issue 25 (19th June 2020) - Wang, Kaiqiang; Liu, Yanfei; Li, Jinjin; Li, Jianfeng
Abstract : A voltage at the millivolt level could be generated by moving ionic droplets on a partially reduced, smooth graphene oxide film. Abstract : Drawing potential has recently been observed in monolayer graphene that can generate electricity upon interaction with water; however, it remains a challenge to generate drawing potential in lower-cost and more stable layered materials. In this study, we used an electro-fluidic assembly method to fabricate a smooth reduced graphene oxide (rGO) film. A voltage in the millivolt magnitude was generated by controlling the movement of an ionic solution droplet over this rGO film, and the type and concentration of the ionic solution and the volume and sliding velocity of the droplet could directly influence the voltage amplitude. The direct observation of electrical double repulsive force between the rGO film and a silica probe confirms the existence of an electric double layer (EDL) on the rGO film, which leads to the formation of a micro-capacitor at the droplet/rGO film interface. Electricity was generated due to the transfer of electrons along the rGO film through the adsorption and desorption of cations in the solution, which is determined by the surface charge density on the rGO film. Because the rGO film is flexible and can be easily transferred onto a soft substrate, it has promising applications in wearable energy-harvesting devices and self-powered micro-electromechanical systems.